2023
DOI: 10.1001/jamanetworkopen.2023.13162
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Maternal Labor-Related Complications and Neonatal Outcomes Following Elective Induction of Labor at 39 Weeks of Gestation vs Expectant Management

Abstract: ImportanceElective induction of labor at 39 weeks of gestation is common. Thus, there is a need to assess maternal labor-related complications and neonatal outcomes associated with elective induction of labor.ObjectiveTo examine maternal labor-related complications and neonatal outcomes following elective induction of labor at 39 weeks compared with expectant management.Data SourcesA systematic review of the literature was conducted using the MEDLINE (Ovid), Embase (Ovid), Cochrane Central Library, World Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 45 publications
(186 reference statements)
1
4
0
Order By: Relevance
“…This would support previous research advocating for universal induction at 39 to improve the results of the perinatal outcome [23,24]. However, the decision should be agreed with the patient, since induction (especially in nulliparous women) also entails risks [23][24][25][26], such as shoulder dystocia [23].…”
Section: Discussionsupporting
confidence: 74%
“…This would support previous research advocating for universal induction at 39 to improve the results of the perinatal outcome [23,24]. However, the decision should be agreed with the patient, since induction (especially in nulliparous women) also entails risks [23][24][25][26], such as shoulder dystocia [23].…”
Section: Discussionsupporting
confidence: 74%
“…A systematic review found that inducing labour at 39 weeks was associated with improved neonatal outcomes in both in nulliparous and primiparous women. However, in nulliparous women, induction of labour was associated with shoulder dystocia [ 20 ]. The external validity of these studies [ 19 , 20 ] for the Norwegian practice is questionable since intervention rates during spontaneous and induced labour are substantially lower [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, in nulliparous women, induction of labour was associated with shoulder dystocia [ 20 ]. The external validity of these studies [ 19 , 20 ] for the Norwegian practice is questionable since intervention rates during spontaneous and induced labour are substantially lower [ 21 , 22 ]. There is some evidence that induction of labour may reduce perinatal death and morbidity [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…When the hazards to the mother and unborn child of carrying a pregnancy to term exceed those of an accelerated delivery, IOL is advised. IOL may be necessary for post-term pregnancies that are older than 41 weeks, for medical conditions such as hypertension or pre-labor rupture of the membranes, or in situations where there may be inadequate fetal growth [8,9] . Induction without any medical indication is known as eIOL.…”
Section: Discussionmentioning
confidence: 99%